Research on model fitting and strength characteristics of critical state for expansive soil - Li, Zhiqing; Tang, Chuan; Hu, Ruilin; Zhou, Yingxin (Journal of Civil Engineering and Management, 2013)
According to Mengzi expansive soil, consolidated drained tests and undrained tests are carried on under saturated and remoulded conditions. The stress-strain characteristics of saturated soil are researched systematically under different confining pressure, initial dry density, initial water content, shearing rate and drainage condition. The inherent unity of diversity of shearing strength for the same samples measured by different experimental methods is indicated according to the normalization of critical state test results. And the failure lines in p‘ - q - ν space of remoulded saturated expansive soil under consolidated drained and undrained conditions are attained. The hyperbolic curve model can fit well the weak hardening stress-strain curves and the exponential curve model can fit the weak softening stress-strain curves. The test results can provide technical parameters and theoretical help for shearing strength variation of slope during rainfall and strength state of soil structure in normal water level.